AVAILABILITY OF METADATA IN LINKED DATE FOR DIGITAL REPOSITORIES - Arakaki, Felipe Augusto; Coneglian, Caio Saraiva [UNESP]; Amorim da Costa Santos, Placida Leopoldina Ventura [UNESP]; Santarem Segundo, Jose Eduardo (Edit Um-ediciones Univ Murcia, 2019)
Considering the expansion of scientific production in digital information environments and the new forms of data availability following the principles of Linked Data, the objective is to discuss possibilities of relationships of datasets and semantic enrichment of metadata in digital repositories and present a model of conversion of records in RDF. It is a theoretical and exploratory research, performing a bibliographic review on digital repositories and Linked Data. In this way, we have demonstrated possibilities of the conversion process, identifying databases, vocabularies and standards that must be adopted so that the generated data is enriched semantically. The work presented a model that reflects the steps that must be taken in the process of making available the metadata of a digital repository in Linked Data. It is concluded that the integration between digital repositories and Semantic Web technologies allows the availability of data in Linked Data, which provides new means for the dissemination and integration of resources on Web.
Keywords: Semantic Web; Linked Data; digital repositories; metadata